2021
DOI: 10.1093/ibd/izab086
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Diversion for Perianal Crohn Disease in the Era of Biologic Therapies: A Multicenter Study

Abstract: Background The natural history of perianal Crohn disease (PCD) after fecal diversion in the era of biologics is poorly understood. We assessed clinical and surgical outcomes after fecal diversion for medically refractory PCD and determined the impact of biologics. Methods We performed a retrospective, multicenter study from 1999 to 2020. Patients who underwent fecal diversion for refractory PCD were stratified by diversion ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…Similar to McCurdy et al, 1 we concluded that objective fistula closure is much lower with FD than anticipated and desired by clinicians. Additionally, we showed that FD was associated with significant stoma-related morbidity.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Similar to McCurdy et al, 1 we concluded that objective fistula closure is much lower with FD than anticipated and desired by clinicians. Additionally, we showed that FD was associated with significant stoma-related morbidity.…”
supporting
confidence: 88%
“…To the Editors, We read the article by McCurdy et al with great interest. 1 Perianal fistulas are seen in up to 24% of patients with Crohn's disease (CD), are often refractory to medical therapy, and result in significant impairment of quality of life. 2 Fecal diversion (FD) surgery is used to manage refractory perianal CD fistulas (pCDs), with a meta-analysis showing 63% clinical improvement 3 ; however, objective data on fistula healing rates, such as no fistula drainage despite gentle finger compression, exam under anesthesia (EUA), magnetic resonance imaging (MRI), or endoscopic ultrasound, are often not reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many prior studies on FD have described symptomatic improvement but do not report actual objective fistula healing rate as determined by no fistula drainage despite gentle finger compression, exam under anesthesia, MRI pelvis, or endoscopic ultrasound. Our recent study evaluating fistula healing after FD as a primary endpoint showed fistula healing of 40% and is similar to two recent multicenter studies which reported between 36.8-42.2% fistula healing after FD, which is much lower than the summary estimate of 63.8% used in our study (8)(9)(10). At the same time, the MSC fistula healing rates are obtained from a robust phase III clinical trial (ADMIRE-CD) (5), and is similar to those reported in multiple studies including In conclusion, our study demonstrates that MSCs are more cost effective than FD for refractory pCD in an academic medical center.…”
Section: Discussionsupporting
confidence: 90%
“…Twenty percent of the patients ultimately required colectomy. A recent study evaluated the long-term outcomes of 82 patients with fecal diversion with or without proctectomy ( McCurdy et al., 2021 ). Fistula healing occurred more frequently after diversion with proctectomy (in 83% of cases) than after diversion without proctectomy (53%).…”
Section: Surgical Treatmentmentioning
confidence: 99%